Hypoxic Wharton’s Jelly Stem Cell Conditioned Medium Induces Immunogenic Cell Death in Lymphoma Cells - Hao Daniel Lin; Chui-Yee Fong; Arijit Biswas; Ariff Bongso (Stem Cells International)
Mesenchymal stem cells from Wharton’s jelly of the human umbilical cord (hWJSCs), and the conditioned medium (hWJSC-CM) prepared from them, were shown to be tumoricidal on many cancers. However, these tumoricidal effects were observed in hWJSCs grown under normoxic conditions of 21% oxygen in the laboratory. Since oxygen concentrations in the stem cell niche or physiological microenvironment are hypoxic and help to maintain stemness properties, the objective of this work was to evaluate whether there were differences in the tumoricidal properties of hWJSC-CM grown in 21% O2 (normoxic) or 5% O2 (hypoxic) environments. The results showed that hWJSCs grown under normoxic or hypoxic conditions showed no distinct morphological differences in culture and remained positive in trilineage differentiation into adipocytes, osteocytes, and chondrocytes. Hypoxic hWJSCs expressed the mesenchymal stem cell surface markers CD105, CD90, CD73, CD146, and CD108 similar to normoxic hWJSCs but were negative for the hematopoietic markers CD14, CD19, CD34, CD45, CD117, and HLA-DR. Hypoxic hWJSC-CM produced a significantly greater reduction in cell viability and a significantly greater increase in apoptosis, oxidative stress, and lipid peroxidation in human lymphoma cells compared to normoxic hWJSC-CM. Hypoxic hWJSC-CM also produced significantly greater expression of immunogenic cell death (ICD) hallmarks such as surface-bound calreticulin, HSP70, HSP90, and high mobility group binding 1 proteins and significantly decreased expression of the defense molecules CD47 and PD-L1. This study showed that the tumoricidal effect of hypoxic hWJSC-CM was superior to normoxic hWJSC-CM and should be the preferred choice of preparing hWJSC-CM for the induction of ICD on lymphoma cells.